Low-dose ionizing radiation as a factor increasing cardiovascular mortality: is there a risk from multiple computed tomographies in the context of COVID-19 pandemic? - A. N. Koterov; L. N. Ushenkova (Российский кардиологический журнал)
The review aim was to familiarize biomedical professionals with the latest evidence-based data on the effect of sparsely ionizing radiation (X-ray, γ- and β-radiation) on cardiovascular mortality (ICD-9: 390-459; ICD-10: I00-I99), which is especially important during the coronavirus disease 2019 (COVID-19) pandemic due to the increased use of computed tomography (CT) and X-ray procedures. Information is presented on the officially accepted range of radiation doses (very low doses — 0-0,01 Gy, low doses — 0,01-0,1 Gy, moderate doses — 0,1- 1,0 Gy, high doses — over 1 Gy). The evolution of ideas about the effects of radiation on the prevalence of cardiovascular diseases is discussed: from high and very high doses to the declaration in recent years of the possible effect of low doses. The statements from the documents of authoritative radiation organizations (UNSCEAR, ICRP, NCRP, EPA, etc.) are given, according to which the threshold for increasing cardiovascular mortality is 0,5 Gy (range of moderate doses), and there are no epidemiological justifications for the effects of low doses. According to a data for six countries, the maximum cumulative doses from multiple CT scans for COVID-19 diagnosis are one order less than the threshold dose, and the average cumulative doses are two orders less. Data on the absence or low risk of cancer after CT for this reason are also presented.